2012
DOI: 10.1111/bjd.12000
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and other patient‐reported outcomes improve after patients with psoriasis with suboptimal response to other systemic therapies are switched to adalimumab: results from PROGRESS, an open‐label Phase IIIB trial

Abstract: Adalimumab treatment improved sleep outcomes and other patient-reported outcomes including health-related quality of life, work productivity, daily activity and disease-related pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
59
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 33 publications
7
59
3
2
Order By: Relevance
“…Further, in another study where telephone and e-mail surveys were conducted, Callis Duffin et al [11] found that 49.5% of patients with psoriasis claimed that their sleep was affected negatively by psoriasis at least once a month. Our results were in accordance with the results of previous studies showing sleep disturbances in patients with psoriasis [3,12,13]. The common conclusion in these studies was that understanding the origin of comorbidities, including sleep problems, in patients with psoriasis may help improve daily living and future treatment of the disease [3].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Further, in another study where telephone and e-mail surveys were conducted, Callis Duffin et al [11] found that 49.5% of patients with psoriasis claimed that their sleep was affected negatively by psoriasis at least once a month. Our results were in accordance with the results of previous studies showing sleep disturbances in patients with psoriasis [3,12,13]. The common conclusion in these studies was that understanding the origin of comorbidities, including sleep problems, in patients with psoriasis may help improve daily living and future treatment of the disease [3].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, sleep disturbance should be considered as a risk factor for the development of psoriasis [14]. Our study presents additional confirmation that besides sleep disturbances, patients with psoriasis have substantially impaired sleep quality compared with general healthy people [11,12,15].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations